Molting in C. elegans. Issue 1 (2nd January 2017) - Lažetić, Vladimir; Fay, David S.
ABSTRACT: Molting is an essential developmental process for the majority of animal species on Earth. During the molting process, which is a specialized form of extracellular matrix (ECM) remodeling, the old apical ECM, or cuticle, is replaced with a new one. Many of the genes and pathways identified as important for molting in nematodes are highly conserved in vertebrates and include regulators and components of vesicular trafficking, steroid-hormone signaling, developmental timers, and hedgehog-like signaling. In this review, we discuss what is known about molting, with a focus on studies in Caenorhabditis elegans . We also describe the key structural elements of the cuticle that must be released, newly synthesized, or remodeled for proper molting to occur.